Developing and implementing an English-Spanish literary parallel audio-textual corpus for data-driven ESL learning - Lang, Michael; Gómez Guinovart, Xavier (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2022)
The purpose of this paper is to present the LITTERA corpus, an English-Spanish literary parallel speech corpus created for the purpose of language learning, and to sketch out a few pedagogical applications for the study of English phonology by Spanish-speaking language learners. It is composed of 25 literary texts that have been aligned with the Spanish translation and are accompanied by audio from the corresponding audiobooks. In this article, we will detail its conception, composition and features at length, as well as provide a few examples of how LITTERA can be applied in language learning, particularly within the realm of oral comprehension and speech production.